Sustainable Development in Public Administration: Research, Practice, and Education - RĂDULESCU, Carmen-Valentina; MĂNESCU, Cătălin-Octavian; POPESCU, Maria-Loredana; BURLACU, Sorin (European Journal of Sustainable Development, 2023)
Sustainable development has become a critical concern for public administration, spanning research, practice and education. The aim of this paper is to explore the current state of sustainable development in public administration from the perspective of recent research, specialist student practice and university education. The research carried out considered the challenges and opportunities associated with the implementation of sustainable development in public administration. it also highlighted the innovative approaches and tools that are being developed to address these challenges. The results obtained contribute to a better understanding of how sustainable development can be integrated into public administration practices, policies and curricula and provide insights into actions that can be taken to promote its implementation. The methodology for this paper involved a comprehensive review of the literature on sustainable development in public administration, including academic articles, books, and reports from international organizations. Case studies of sustainable development practices in public administration were also analyzed to provide practical insights into how sustainable development is implemented in practice. Interviews were conducted with experts in the field to gather additional insights into the challenges and opportunities associated with sustainable development in public administration. Data collected through literature review, case studies and interviews were analyzed thematically to identify key themes and patterns. The findings were used to develop a comprehensive understanding of sustainable development in public administration and to provide insights into the challenges and opportunities for its implementation. By identifying the challenges and opportunities associated with sustainable development in public administration, the paper highlights the need for innovative approaches and tools to promote its implementation. Keywords: public administration, sustainable development, research, practice, education